Peroral endoscopic myotomy for esophageal achalasia: Clinical impact of 28 cases. Issue 1 (14th April 2013) - Minami, Hitomi; Isomoto, Hajime; Yamaguchi, Naoyuki; Matsushima, Kayoko; Akazawa, Yuko; Ohnita, Ken; Takeshima, Fuminao; Inoue, Haruhiro; Nakao, Kazuhiko
Abstract : Background: The aim of the present study was to clarify the efficacy of peroral endoscopic myotomy (POEM) for esophageal achalasia. Patients and Methods: Twenty‐eight esophageal achalasia patients who underwent POEM in our institution between August 2010 and October 2012 were enrolled. Under general anesthesia with tracheal intubation, initial incision was made on the anterior wall of the esophagus after submucosal injection. Submucosal tunnel was created and extended below the lower esophageal sphincter (LES) onto the gastric cardia. Subsequently, myotomy was done using triangle tip knife. After confirmation of smooth passage of scope through the esophagogastric junction, the entry was closed. Esophagogram and manometry study was done before and after the procedure. Also, subjective symptom score and Eckardt score were assessed before and 3 months after POEM. Results: POEM was successfully done in all cases without any severe complications such as perforation and mediastinitis.Mean procedure time was 99.1 min (range 61–160) and mean myotomy length was 14.4 cm (range 10–18). Significant improvement was achieved in both esophagogram and endoscopic findings. Mean LES pressure was 71.2 mmHg (35.8–119.0) and 21.0 mmHg (6.7–41.0) before and after the procedure ( P  < 0.05), respectively. Mean Eckardt score was 6.7 (3–12, median 7) and 0.7 (0–3, median 1) before and 3 months after POEM, respectively ( P  < 0.05). Symptomatic gastroesophageal reflux disease that was easily controlled by the usual dose of proton pump inhibitor was seen in six cases (21.4%) after the procedure. Conclusion: POEM could be a curative standard treatment of choice for esophageal achalasia.